2015
DOI: 10.1002/jocc.12020
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injury and Suicide: Practical Information for College Counselors

Abstract: The relationship between self–injury (SI) and suicide is largely unclear. However, researchers have suggested that clients who self–injure are at a heightened risk of suicide (Chapman & Dixon–Gordon, ; Toprak, Cetin, Guven, Can, & Demircan, ). Thus, it is important that college counselors be knowledgeable about both SI and suicide. In this article, the authors provide an overview of SI and suicide, as well as practical information for college counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…College MHPs . Currently, there are a number of publications outlining best practices for MHPs when responding to NSSI (Klonsky et al, ; Washburn et al, ), with some specific to college contexts (Lewis & Arbuthnott, ; Whisenhunt et al, ). Although there are some challenges unique to college mental health services, overall, the response shares many commonalities with that of community‐based MHPs to NSSI.…”
Section: Effective Responses To Nssi On College Campusesmentioning
confidence: 99%
See 1 more Smart Citation
“…College MHPs . Currently, there are a number of publications outlining best practices for MHPs when responding to NSSI (Klonsky et al, ; Washburn et al, ), with some specific to college contexts (Lewis & Arbuthnott, ; Whisenhunt et al, ). Although there are some challenges unique to college mental health services, overall, the response shares many commonalities with that of community‐based MHPs to NSSI.…”
Section: Effective Responses To Nssi On College Campusesmentioning
confidence: 99%
“…Notwithstanding the growth of empirical knowledge in this area, NSSI is the subject of numerous myths and misconceptions (Lewis & Heath, ; Lewis, Mahdy, Michal, & Arbuthnott, ). Moreover, college professionals report witnessing an increase in NSSI‐related concerns in their work with students yet, unfortunately, report insufficient knowledge and/or confidence to effectively address or manage NSSI (Whisenhunt et al, ; Whitlock et al, ).…”
mentioning
confidence: 99%
“…ollege counseling centers continue to experience rising demand for services (LeViness et al, 2018). Up to 35% of college students experience a diagnosable mental health disorder (Auerbach et al, 2018), and suicide and self-injury are concerns for college counselors (Lewis et al, 2019;Whisenhunt et al, 2015). Furthermore, college counseling services often have wait lists that are not easily downsized (Epstein, 2015).…”
mentioning
confidence: 99%
“…Estimates of suicidal ideation among college students range from 32% to 70% (Whisenhunt et al, ), and suicide is the second leading cause of death among young adults ages 18 to 24 years (Centers for Disease Control and Prevention, ). Whisenhunt et al () identified suicidal ideation and self‐injury as significant predictors of suicidal acts, given that 7% of college students who experience suicidal ideation go on to make a suicide attempt. According to the CCMH (), approximately 20% of college students seeking mental health services have seriously considered suicide within the past year.…”
mentioning
confidence: 99%